Factors Influencing the Decision to Attend a Pediatric Emergency Department for Nonemergent Complaints. Issue 9 (September 2015) - Smith, Victoria; Mustafa, Majd; Grafstein, Eric; Doan, Quynh
Abstract : Objective: The objective of this study was to explore the factors associated with parents' decisions to bring their children to the pediatric emergency department (PED) for nonemergent concerns. Methods: We conducted a cross-sectional survey at a tertiary-care, pediatric referral center emergency department. We surveyed caregivers of children triaged to low-acuity levels using the Pediatric Canadian Triage and Acuity Scale. We used descriptive statistics to report the proportion of patients who have a primary care physician, who attempted to contact any health care providers prior to coming to the PED, and other factors surrounding the decision to come to the PED. Results: We approached 340 families, of which 300 were enrolled (uptake rate, 88.2%). We found that 32% (95% confidence interval, 0.26–0.37) attempted to contact another health care provider prior to coming to the PED, and 59% (95% confidence interval, 0.48-0.69) of those respondents were specifically instructed to come to the PED. The top 3 reasons for coming to the British Columbia Children's Hospital PED were (1) that it specializes in children, (2) child has medical issues previously managed at the same hospital, and (3) closest location to patient. Conclusions: Despite the majority of patients having a primary care physician, less than half of them actually contacted these providers (or another health care provider) before presenting to the PED for their nonurgent illness or injury. Of these, nearly two thirds were specifically instructed to come to the PED by the health care provider in the community.